The idiot - Dostoyevsky, Fyodor, 1821-1881 (Floating Press, 2009)
Prince Myshkin, a good yet simple man, is out of place in the corrupt world created by Russia's ruling class.
Keywords: Princes -- Russia -- Fiction.; Good and evil -- Fiction.; Triangles (Interpersonal relations) -- Fiction.; Russia (Federation) -- Social conditions -- 1801-1917 -- Fiction.; Princes -- Russie -- Romans, nouvelles, etc.; Triangle (Relations humaines) -- Romans, nouvelles, etc.; Good and evil; Princes; Social conditions; Triangles (Interpersonal relations); Russia; Russia (Federation); 1801-1917; Fiction